Implementation of Game-Assisted Interactive Demonstration on Students' Problem-Solving Skills and Digital Literacy in the Immune System - Ruddy Indra Frahasta; Aa Juhanda; Gina Nuranti (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
This study aims to ascertain whether there is an impact on students' problem-solving skills and digital literacy. The research method uses Matching Only Pretest-Posttest Control Group Design. Fifteen students each from the experimental class and the control class made samples. The experimental class received an Interactive Demonstration model with the help of games. Tests of problem-solving skills and digital literacy and surveys asking respondents about their responses were used to obtain data. The analysis findings suggest that game-assisted Interactive Demonstration models can support and significantly influence high school students' capacity for problem-solving and digital literacy regarding immune system materials. The results showed that students in experimental classes on immune system content had high problem-solving skills, as seen by an average post-test score of 82, with an average N-Gain score of 0.74. According to the results of the hypothesis test, H1 is accepted because the significance value of Sig (2-tailed) is 0.000. The average score for digital literacy at level 4 is 56.77, with criteria usually meeting expectations. The average score on the response questionnaire was 69.33, which is excellent. The instrumental results in this study show how interactive demonstrations through games increase students' capacity for problem-solving regarding immune system content.This study aims to ascertain whether there is an impact on students' problem-solving skills and digital literacy. The research method uses Matching Only Pretest-Posttest Control Group Design. Fifteen students each from the experimental class and the control class made samples. The experimental class received an Interactive Demonstration model with the help of games. Tests of problem-solving skills and digital literacy and surveys asking respondents about their responses were used to obtain data. The analysis findings suggest that game-assisted Interactive Demonstration models can support and significantly influence high school students' capacity for problem-solving and digital literacy regarding immune system materials. The results showed that students in experimental classes on immune system content had high problem-solving skills, as seen by an average post-test score of 82, with an average N-Gain score of 0.74. According to the results of the hypothesis test, H1 is accepted because the significance value of Sig (2-tailed) is 0.000. The average score for digital literacy at level 4 is 56.77, with criteria usually meeting expectations. The average score on the response questionnaire was 69.33, which is excellent. The instrumental results in this study show how interactive demonstrations through games increase students' capacity for problem-solving regarding immune system content.This study aims to ascertain whether there is an impact on students' problem-solving skills and digital literacy. The research method uses Matching Only Pretest-Posttest Control Group Design. Fifteen students each from the experimental class and the control class made samples. The experimental class received an Interactive Demonstration model with the help of games. Tests of problem-solving skills and digital literacy and surveys asking respondents about their responses were used to obtain data. The analysis findings suggest that game-assisted Interactive Demonstration models can support and significantly influence high school students' capacity for problem-solving and digital literacy regarding immune system materials. The results showed that students in experimental classes on immune system content had high problem-solving skills, as seen by an average post-test score of 82, with an average N-Gain score of 0.74. According to the results of the hypothesis test, H1 is accepted because the significance value of Sig (2-tailed) is 0.000. The average score for digital literacy at level 4 is 56.77, with criteria usually meeting expectations. The average score on the response questionnaire was 69.33, which is excellent. The instrumental results in this study show how interactive demonstrations through games increase students' capacity for problem-solving regarding immune system content.